Development of Length Measurement Materials using Adobe After Effects - Uswatun Chasanah; Aninditya Sri Nugraheni; Mazarul Hasan Mohamad Hanapi (Profesi Pendidikan Dasar, 2021)
This study aims to (1) produce a video of length measurement material through Adobe After Effects software. (2) determine the validity and feasibility of the developed video. (3) Knowing the student's response to the video length measurement material. This study uses the Research and Development (RD) method, which is modified from the 4D model, data collection techniques by observation, interviews, questionnaires, and documentation. The data analysis technique is done by converting qualitative data into quantitative data. The quality of the video development of length measurement material based on the assessment of mathematicians scored 5.0 with a good predicate, learning media experts got a score of 4.7 with a good predicate, and linguists got a score of 4.75 with an appropriate predicate. The teacher's assessment obtained a score of 5.0 with a felicitous predicate. The results of the limited video trial obtained a percentage of 100%, meaning that the average student gave a positive response to the material developed in the video